Does producing scientific articles lead to Paralympic podiums? - Pilon, F.; Prince, F. (Biomechanics, 2024)
The Olympic/Paralympic Games are world events that promote countries and their participants, and more particularly, those winning medals. The potential link between a country`s scientific productivity and its podium wins remains unknown for the Paralympic Games. This study aimed to (1) quantify the link between the production of Paralympic scientific articles and the medals won by countries during Summer/Winter Paralympic Games between 2012 and 2022, and (2) select the five most important articles published for all Paralympic sports. A bibliographic search of the Web of Science, PubMed, and Google Scholar databases was conducted. From the 1351 articles identified, 525 fulfilled the inclusion/exclusion criteria. The results showed a greater (7x) production of scientific articles relating to the Summer Paralympics compared to those relating to the Winter Paralympics. For the Summer Paralympics, there was a strong correlation (r = 0.79) between the number of medals and the number of scientific articles produced by a given country, while a low correlation (r = 0.12) was observed for the Winter Paralympics. Biomechanics-related articles represent almost 50% of the overall Paralympic publications. In conclusion, there is a strong link between scientific productivity and the number of medals won for the 2012-2022 Paralympic Games. Parasport Federations are strongly encouraged to promote the publication of more Paralympic research articles.